Dating violence experienced: How interpersonal communication shows it all - Arbay, Evi Aryati; Kurniawan, Devyana; van Eymeren, MargarethaMargawati (Technium Social Sciences Journal, 2020)
This study examined interpersonal communiation between perpetrators and victims of dating violence. Interpersonalcommunication that carried by 3 survivors who will also tell what has been said by perpetrator through their experiences. The research conducted by deep interview with all of subjects those as participants and a psychologist. In order to get the core words of the languange that has been used when communicating with each other. That implies interpersonal communication is important as way to read how by using certain words or sentences in interpersonl communication can build something that has impact for one who spoken to person who in romance relationship. It can created self esteem, interdependence and secure feeling or as the opposite when dating violence occured; insecure, fear, shame, humiliate, less confidence or gaslighting. Those are the findings through particular evidences base on survivor narrated of interpersonal communication with perpetrator that has been told to researcher about how they were experiences dating violence, and physical evidences has proofed how it operates. The dating violence can perpetuated and have countless negative impact when the victims survivors still tolerate such behaviors from the perpetrator (boyfriend/lover), and do not aware that those abusive treatments are must not to be accepted.